Otvoreni prelomi karlice – rezultati multi-institucionalne studije - Mladenović, Marko; Stoiljković, Predrag; Lalić, Ivica; Harhaji, Vladimir; Krstić, Andrija (Vojnosanitetski pregled, 2022)
Background/Aim. Open pelvic fractures are devastating, rare injuries with high mortality. Leading causes of mortality are the following: hemorrhage, infection, and associated injuries. The aim of this study was to point out methods of treating these injuries and a great number of prognostic mortality factors. Methods. In the period from January 2011 to December 2015, 221 patients with pelvis ring fractures were treated at three large clinical centers in Serbia, of which 13 (5%) patients had an open fracture type. We have classified pelvic ring fractures according to the Young-Burgess classification. We have classified injuries according to Gustilo at I, II, and III degrees, and the location of the wound according to Faringer classification was distributed in zone I, II, and III. Urogenital and intra-abdominal injuries were monitored, and the severity of injuries was determined according to Severity Score Injury (ISS) and Trauma Score (TS). Results. There were 6 (46%) women and 7 (54%) men with an average age of 41 year (13–76). Injuries from traffic trauma were dominant. The most common causes of pelvic ring fracture were antero-posterior compression – 6 (46%), lateral compression – 4 (31%), and vertical force in 3 (23%) patients. Dominant injuries were types I and II according to Gustilo and zone I according to the Faringer classification. There were 6 (46%) patients with urogenital injuries and the same number with intra-abdominal injuries, of which 3 (23%) patients had been treated with colon resection and diversion. Due to abundant hemorrhage and hypovolemic shock, two patients died, and another one died after three days due to sepsis and multisystem organ failure. Conclusion. Open pelvic fractures have a high mortality rate due to: hemorrhage, infection, associated abdominal and genitourinary tract injuries, ISS > 25, TS < 8, and the age of patients > 65 years.
Keywords: fractures, open; injury severity score; mortality; orthopedic procedures; pelvis; risk factors